2011
DOI: 10.1063/1.3599450
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of sub-bandgap absorption in chalcogen-hyperdoped silicon

Abstract: Silicon doped with nonequilibrium concentrations of chalcogens using a femtosecond laser exhibits near-unity absorption of sub-bandgap photons to wavelengths of at least 2500 nm. Previous studies have shown that sub-bandgap absorptance decreases with thermal annealing up to 1175 K and that the absorption deactivation correlates with chalcogen diffusivity. In this work, we show that sub-bandgap absorptance can be reactivated by annealing at temperatures between 1350 and 1550 K followed by fast cooling ͑Ͼ50 K / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 12 publications
6
37
1
Order By: Relevance
“…Reactivation has been previously reported when deactivated hyperdoped silicon was irradiated with fs laser pulses or heated to temperatures above 1350 K followed by fast cooling (e.g., in silicone oil, yielding estimated cooling rates of about 250 K/s). 32 The reactivation we observe after ns laser annealing, however, is more complete than what has been previously reported and produces or maintains high crystallinity, unlike reactivation by fs laser pulses, which typically produces a layer of amorphous silicon. 29 We combined thermal and ns laser annealing in sequence to demonstrate the design flexibility provided by combining equilibrium with non-equilibrium processing techniques ( Figure 7).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Reactivation has been previously reported when deactivated hyperdoped silicon was irradiated with fs laser pulses or heated to temperatures above 1350 K followed by fast cooling (e.g., in silicone oil, yielding estimated cooling rates of about 250 K/s). 32 The reactivation we observe after ns laser annealing, however, is more complete than what has been previously reported and produces or maintains high crystallinity, unlike reactivation by fs laser pulses, which typically produces a layer of amorphous silicon. 29 We combined thermal and ns laser annealing in sequence to demonstrate the design flexibility provided by combining equilibrium with non-equilibrium processing techniques ( Figure 7).…”
Section: Discussioncontrasting
confidence: 41%
“…30 31 After deactivation, the sub-bandgap optical absorptance can be reactivated partially by heating and fast cooling. 32 Fifth and finally, sub-bandgap optoelectronic response has been observed both in flat crystalline silicon hyperdoped with gold and in sulfur-hyperdoped black silicon, demonstrating that hyperdoping can indeed produce subbandgap optoelectronic response in semiconductor materials. 33 34 The properties of hyperdoped silicon and hyperdoped black silicon imply some design guidelines for hyperdoped optoelectronic devices.…”
Section: Introductionmentioning
confidence: 93%
“…1,[3][4][5][7][8][9] This suggests that optical hyperdoping-the introduction of dopants at high concentrations with pulsed lasers-may be a method to tailor the band structure of Si to engineer properties for enhanced photovoltaic or infrared detector applications. 10,11 Multiple studies have examined the thermodynamic and optoelectronic properties of this hyperdoped material to understand the nature of the sub-bandgap absorptance [12][13][14][15] and have shown that the dopants can be manipulated through thermal processing to engineer optical and electronic properties. 12,14 However, the dopant chemical state and its evolution during annealing remains unknown, limiting the potential defect engineering of this material.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Multiple studies have examined the thermodynamic and optoelectronic properties of this hyperdoped material to understand the nature of the sub-bandgap absorptance [12][13][14][15] and have shown that the dopants can be manipulated through thermal processing to engineer optical and electronic properties. 12,14 However, the dopant chemical state and its evolution during annealing remains unknown, limiting the potential defect engineering of this material.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies are for defects in the impurity limit and various approaches have been proposed to overcome the doping limit in semiconducting or insulating materials 5 . For many semiconductors, however, hyperdoping (doping to a high concentration) is required to improve the electronic conductivity or modify the host band structure for nextgeneration electronic and optical devices, such as bipolar transistors, spintronic devices, or high-efficiency solar and photoelectrochemical cells for energy production [6][7][8][9] , especially as the size of the devices is reduced to the nanoscale 10,11 .…”
Section: Introductionmentioning
confidence: 99%